Creative utilization of poetry in primary education: the case of Odysseas Elytis in kindergarten - Παυλοπούλου, Ζωή-Παρασκευή; Τσιτσανούδη-Μαλλίδη, Νικολέττα (Επιστημονική Επετηρίδα Παιδαγωγικού Τμήματος Νηπιαγωγών Πανεπιστημίου Ιωαννίνων, 2024)
In this paper we attempt to approach the issue of poetry in the modern Greek school, specifically at the kindergarten level, on a theoretical and practical basis. Starting from the need to free poetry and its pedagogical utilization from a conventional and sterile approach, we focus on the prerequisites for an essential didactic use of poetry, and we highlight the qualities that make Elytis’ s poetry accessible to kindergarten students. On a practical level we propose ideas and activities that serve a creative use of poetry in the context of preschool education.